A question of food intake: The impact of living arrangement and meal factors on total daily caloric intake. Issue 2 (2nd April 2020) - Sorenson, Kaléi E.; Rice, Jennifer; Droms Hatch, Courtney
Abstract: There has been dramatic weight gain among college students during their collegiate years. A food diary can give much insight of a college student's life. The purpose of this study is to analyze the food intake of college-aged students taking in factors such as the size of meal, the foods being eaten, the location of the meal, and if the meal was eaten with others. The results of this study suggest that being male, eating breakfast, and eating more snacks relative to the number meals increases daily caloric intake. On the other hand, being female and eating more meals at home will result in a lower daily caloric intake.